MODEL REGRESI KINERJA KARYAWAN BERDASARKAN SISTEM INFORMASI AKUNTANSI, PENGENDALIAN INTERNAL, DAN MOTIVASI KERJA PADA PT. SENTRALSARI PRIMASENTOSA (DEPO CLEO KEDIRI) - Novita Effendi, Elviana; Tohari, Amin; Solikah, Mar'atus (Universitas Nusantara PGRI Kediri, 2022)
This study aims to analyze the effect of accounting information systems, internal control, and work motivation on employee performance at the Cleo Depo Kediri. This research uses a quantitative approach with a causal associative survey research method. The data analysis method uses multiple linear regression, classical assumption test, determinant coefficient test (R2) and hypothesis test. The results of this study indicate that the accounting information system partially has a significant effect on employee performance. Partial internal control has a significant effect on employee performance. Work motivation partially has a significant effect on employee performance. Simultaneously accounting information system, internal control and work motivation affect the performance of employees at PT. Sentralsari Primasentosa (Depo Cleo Kediri). This study uses the latest data, namely 2022.